O teorema da acomodação e suas aplicações - Fonseca, Fábio Rosa da (1986)
In this work, the basic concepts related to the plastic design of structures are reviewed. The advantages and some methods of the plastic design are presented. The shake-down problem is studied. The tests of metalic frames carried out by NEAL and SYMONDS are shown and the shake-down theorem is proved, in terms of residual bending moments and residual stresses. Conclusions about the plastic design, taking into account the shake-down theorem, are given. The plastic design of reinforced concrete, according to BAKER and MACCHI, is also commented.